Irreducible traumatic pure hip dislocation by the entrapment of the lateral rotator muscle group of the hip: A case report - Zied Mansi; Saibi Firas; Ben Mahmoud Aymen; Tounsi Abdelkader; Islem Chneti; Hedi Rbai; Wajdi Chermiti; Ali Haggui; Bacem Zaidi; Wael Gazzah (Trauma Case Reports)
Introduction: Irreducibility is a rare complication of pure posterior hip dislocation requiring surgical intervention. Case presentation: We present a case of a 22-year-old female with posterior hip dislocation following a motor vehicle accident. Despite unsuccessful closed reduction attempts, open surgical reduction successfully released the incarcerated muscles and achieved reduction. Follow-up examinations showed excellent functional outcomes without complications. Clinical discussion: Irreducibility remains a rare complication of traumatic posterior hip dislocation. Three possible entities can cause soft tissue incarceration: labral buttonholing, intra-articular osteochondral bodies, and entrapment of the piriformis muscle. The posterior-lateral approach provides excellent exposure of the posterior hip structures, but it carries the risk of injury to the medial circumflex artery. After successfully reducing the dislocation, it is essential to perform a computed tomography (CT) scan to detect any osteochondral lesions, including femoral head impaction. Functional outcomes are better with early mobilization and prompt resumption of weight-bearing. However, femoral head osteonecrosis complicates 52.9 % of hip dislocations reduced beyond 6 h, whereas it occurs in only 4.8 % of dislocations reduced within this timeframe. Conclusion: This case underscores the importance of prompt recognition and appropriate surgical intervention for irreducible hip dislocations to prevent further complications and optimize patient outcomes.